Inverse limits of integral domains arising from iterated Nagata composition - Dobbs, David E.; Fontana, Marco (MATHEMATICA SCANDINAVICA, 2001)
By iterating the type of pullback constructions in which P^rVDs arise by Nagata composition, we are led to study a class of inverse limits A=A_n of integral domains indexed by N. After identifying the prime spectrum, the localizations, and the integral closure of A, we then characterize when, i.a., such (typically infinite-dimensional) A is a Prüfer domain, Bezout domain, divided domain, or P^rVD.